Index assessment of the acoustics of Orthodox churches in Poland. (15th January 2018) - Kosała, Krzysztof; Małecki, Paweł
Highlights: The index method for the acoustic assessment of Orthodox churches is proposed. The results are consistent with the subjective tests of the one group of listeners. The examined Orthodox churches in Poland are ranked according to their acoustics. Abstract: This work describes the problem of acoustics in architectural objects related to Christianity in Poland, especially Orthodox churches, and to a lesser extent, Roman Catholic churches. Ensuring adequate acoustic environments in spaces of religious worship is a difficult task, especially as churches differ from other public facilities, due to sacred and emotional factors. Alongside the issue of the proper acoustic design of worship interiors, due to the wide range of acoustic production, including music and speech, a significant problem is the difficultly of making a uniform assessment of acoustic parameters. The index method for the acoustic assessment of Orthodox churches, adapted from a method dedicated to Roman Catholic churches which was developed within the scope of earlier research, was proposed in the article. Acoustic tests conducted in Orthodox churches in Poland together with surveys and geometric measurements, as well as the architectural style along with other distinguishing features, were presented. The obtained results were compared to the subjective tests conducted in advance for the same architectural objects with the index assessment. The proposed index method for determining the single-number assessment was verified in two Orthodox churches from outside Poland in the index values for the geometric models the design stage, is featured.